2017
DOI: 10.1186/s12970-017-0183-x
|View full text |Cite
|
Sign up to set email alerts
|

Individual fluid plans versus ad libitum on hydration status in minor professional ice hockey players

Abstract: BackgroundDespite exercising in cool environments, ice hockey players exhibit several dehydration risk factors. Individualized fluid plans (IFPs) are designed to mitigate dehydration by matching an individual’s sweat loss in order to optimize physiological systems and performance.MethodsA randomized control trial was used to examine IFP versus ad libitum fluid ingestion on hydration in 11 male minor professional ice hockey players (mean age = 24.4 ± 2.6 years, height = 183.0 ± 4.6 cm, weight = 92.9 ± 7.8 kg). … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
4
0
1

Year Published

2019
2019
2024
2024

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 9 publications
(9 citation statements)
references
References 27 publications
(71 reference statements)
1
4
0
1
Order By: Relevance
“…Using education to alter hydration behavior has resulted in equivocal outcomes [27][28][29]. A total of nine runners in O'Neal et al [10] reported previously measuring change in body mass to determine sweat loss volume before study initiation.…”
Section: Discussionmentioning
confidence: 99%
“…Using education to alter hydration behavior has resulted in equivocal outcomes [27][28][29]. A total of nine runners in O'Neal et al [10] reported previously measuring change in body mass to determine sweat loss volume before study initiation.…”
Section: Discussionmentioning
confidence: 99%
“…Emerson et al prescribed a PHS solution corresponding to ice-hockey players' sweat volume. Players were required to ingest the PHS solution within an hour of practice, finally resulted in a -0.95%BML, whereas drink adlibitum resulted in -1.14%BML [20]. Melo-Marins et al applied a PHS solution offset 80% of sweat loss during a time to exhaustion cycling at 70% of the maximal workload, resulted in a -0.2%BML compared to ad-libitum CON with a (-1.0%BML) [21].…”
Section: Fluid Balancementioning
confidence: 99%
“…Participants have to drink 3-4 bottles of commercially available solutions so that to match their sodium needs, which seems untenable to drink that amount of fluid during a short time frame. Two previous studies prescribed a sodium content in the PHS [20,24]. Ayotte et al suggested PHS can provide sodium supplementation in a beverage, especially for those players who engage in prolonged and high intensity exercise to maintain serum sodium concentration [24].…”
Section: Fluid Balancementioning
confidence: 99%
See 1 more Smart Citation
“…Os participantes que concordaram em participar do estudo foram separados em dois grupos, sendo que o primeiro grupo foi orientado a ingerir líquidos apenas quando sentisse sede, enquanto o segundo grupo foi orientado a ingerir Fonte: Ferreira et al 17 . Em um estudo realizado com 8 atletas profissionais de hóquei no gelo, Emerson et al 18 compararam os efeitos da ingestão de fluidos planejada (IFP) com a ingestão de líquidos ad libitum durante a prática esportiva. Os autores analisaram densidade relativa e coloração urinária, concentrações de sódio e potássio urinário, alterações na massa corporal e volume de líquido ingerido.…”
Section: Eu Hipo Fluidounclassified